Stress analysis of bicycle saddles structural components during different cycling conditions - Giubilato, F.; Petrone, N. (Procedia Engineering, 2014)
The structural behaviour of a bicycle saddle is mainly affected by the shell and the rails properties and by their assembly connections. The knowledge of the stress acting on these components is therefore fundamental for a safe and performing saddle engineering design. The aim of the work was the measurement and analysis of the strain/stress state of shell and rails of a bicycle saddle during real cycling conditions. The shell and the rails of a saddle were instrumented with a total of 16 strain gauge channels, allowing the measurement of the local deformations of shell and rails. Two field test sessions (one for road cycling and one for mountain bike riding) were performed with two professional cyclists different for body height and weight (65 and 76 kg). Reported results regard the analysis of rails cyclic stresses due to road pedalling and of stress cumulative spectra obtained during road and mountain bike sessions. Right and the left portions of the rails were loaded symmetrically. The two testers showed large differences in the pedalling style and in the cycling posture. The stress on the front and rear rails portions was mainly influenced by the cyclist posture and pedalling style. An increase of the road slope caused an increment of the stress range and mean values; the damage ratio between mountain bike and road load spectra for an equivalent cycled distance resulted to range between 6 and 9, depending on the tester involved.